Turning Functions in Optimal Synthesis of Mechanisms - Nadal-Martínez, Fernando; Cabrera-Carrillo, Juan Antonio; Bataller-Torras, Alex; Castillo-Aguilar, Juan Jesús; Ortiz-Fernández, Antonio (The American Society of Mechanical Engineers, 2015)
In this paper turning functions utilization for comparing errors between the coupler point and target trajectory is described. The reason why these functions are used is that the error obtained with them does not depend on displacement and rotation of the fixed link and scale change of the mechanism, so the searching space for the optimization algorithm is reduced. To carry out the mechanism synthesis an algorithm based on natural genetics laws is used. The effectiveness of the proposed method has been demonstrated on two synthesis examples.
Keywords: Computación evolutiva; Mechanism synthesis; Optimization; Differential Evolution; Turning Function